The Mind’s Farthest Reach: Dream-Telepathy in Psychoanalytic Situations: Inquiry and Hypothesis - Aragno, Anna (Signs - International Journal of Semiotics, 2011)
Emerging out of an era when the ‘paranormal’ was viewed with skepticism by the scientific community, Freud steered clear of associating psychoanalysis with dream telepathy or thought transference, phenomena which were reported quite frequently within its domain of inquiry. In later years, however, he advocated that sychoanalysts embark on a serious inquiry of this phenomenon, approaching it as a normal rather than paranormal aspect of unconscious functioning. Inspired by direct experience in my practice, this paper searches for the operative roots of dream telepathy. From within a revised framework of Freud’s first topographical model of mind viewed as a continuum from biological to semiotically mediated organizations of experience and modes of interacting (Aragno 1997, 2008), the inquiry ventures to our distant evolutionary past when evidence of ‘representation’ first appeared, leaving traces of early hominid mental capacities. Supported by contemporary neurobiology and interdisciplinary literature, relevant data is selected and synthesized, piecing together a comprehensive hypothesis. The subject is approached from the perspective of a biosemiotic model of human interaction in which all unconscious processes are viewed as natural rather than supernatural phenomena.